2018
DOI: 10.1080/13697137.2018.1433655
|View full text |Cite
|
Sign up to set email alerts
|

Romosozumab treatment in postmenopausal women with osteoporosis: a meta-analysis of randomized controlled trials

Abstract: In postmenopausal women with osteoporosis who were at high risk for fracture, romosozumab treatment resulted in a significantly lower risk of fracture. Romosozumab 210 mg monthly showed the largest gains in BMD, and was generally well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 25 publications
0
20
0
2
Order By: Relevance
“…A meta‐analysis of six trials showed that romosozumab significantly reduces the risk of new vertebral fracture, non‐vertebral fracture and hip fracture compared with other treatments, and improves BMD. The dose of 210 mg monthly showed the largest gains in BMD.…”
Section: Dual Actions Drug: Romosozumabmentioning
confidence: 99%
“…A meta‐analysis of six trials showed that romosozumab significantly reduces the risk of new vertebral fracture, non‐vertebral fracture and hip fracture compared with other treatments, and improves BMD. The dose of 210 mg monthly showed the largest gains in BMD.…”
Section: Dual Actions Drug: Romosozumabmentioning
confidence: 99%
“…Improving the predictive value of risk calculation tools for osteoporosis, developing similar tools for sarcopenia, and integrating sarcopenia within current calculation tools remain future challenges. A seemingly promising treatment targeting sclerostin (romosozumab) demonstrated a significantly lower rate of fracture in osteoporotic women, mostly in vertebral fractures . However, approval was delayed due to concern over serious cardiovascular events .…”
Section: Emerging Science and Future Questionsmentioning
confidence: 99%
“…A seemingly promising treatment targeting sclerostin (romosozumab) demonstrated a significantly lower rate of fracture in osteoporotic women, mostly in vertebral fractures. 74 However, approval was delayed due to concern over serious cardiovascular events. 75 In addition, the duration and sequence of antiresorptive and boneforming therapy is an ongoing source of debate.…”
Section: Emerging Science and Future Questionsmentioning
confidence: 99%
“…Thus, the inhibition of sclerostin can induce the activation of osteoblasts and promote bone formation (Figure 1 and Figure 2). For therapeutic use in humans, the anti-sclerostin antibody (romosozumab) has been developed for the treatment of osteoporosis, which decreases endogenous levels of sclerostin, allowing for osteogenesis through an improvement in osteoblast survival [117,118,119]. Several authors have reported on the anabolic effect of anti-sclerostin antibody in enhancing the bone formation and fracture healing in animal models [120,121,122,123,124].…”
Section: Anti-sclerostin Antibodymentioning
confidence: 99%